Interview with Simone Pulver - Simone Pulver (economic sociology_the european electronic newsletter, 2020)
What was your motivation to engage in the ASA Task Force on Sociology and Global Climate Change? - I first got involved in this a very long time ago. The National Science Foundation (NSF) and American Sociological Association (ASA) co-ran a workshop in 2008, titled "Sociological Perspectives on Global Climate Change," which was a precursor to the ASA Task Force on Sociology and Global Climate Change, launched in 2010. You remember how it was back then; for a long time, climate change was an issue of interest in other disciplines. [...]
Keywords: 300